Enhancing the coating properties of acrylic/casein latexes with high protein content - Picchio, Matías L. (2017)
Casein-derived materials are highly attractive as a consequence of their environmental friendliness and excellent film-forming properties. Due to the casein hydrophilicity, films containing a large protein content are highly susceptible to water, thus limiting their use in coating applications. A novel approach for synthesizing waterborne acrylic?casein latexes with large content of protein and high degree of compatibilization between both components is presented. The employed synthesis strategy involves the use of a highly methacrylated casein in an emulsifier-free emulsion polymerization of acrylic monomers with the aim of controlling both the fraction of grafted biomaterial and the amount of acrylic chains linked onto the protein backbone. The performance of the resulting materials was evaluated in a water-based coating application. The used methacrylation approach allowed the maximum compatibilization of 33% of casein in the hybrid polymer. The as-obtained casein-derived films were proven to exhibit superior water resistance, which would open a new possibility for designing biobased coatings in several fields.